Flexicurity, wage dynamics and inequality over the life-cycle - Paul Bingley; Lorenzo Cappellari; Niels Westergård-Nielsen (Center for Economic Studies and ifo Institute (CESifo), 2011)
We investigate the relationship between life-cycle wages and flexicurity in Denmark. We separate permanent from transitory wages and characterise flexicurity using membership of unemployment insurance funds. We find that flexicurity is associated with lower wage growth heterogeneity over the life-cycle and greater wage instability, changing the nature of wage inequality from permanent to transitory. While we are in general unable to formally test for moral hazard against adverse selection into unemployment insurance membership, robustness checks suggest that moral hazard is the relevant interpretation.
Keywords: J31; J65; 330; unemployment insurance; wage dynamics; wage inequality; wage instability; Flexicurity; Lohnstruktur; Erwerbsverlauf; Arbeitslosenversicherung; Moral Hazard; Dänemark